Laser Performance of 1% at. Yb : Lu2O3 Ceramic. (12th April 2012) - Pirri, Angela; Toci, Guido; Vannini, Matteo
Abstract : We present the performance of a laser prototype based on 1% at. Yb : Lu 2 O 3 ceramic, longitudinally pumped in quasi-CW regime at 968 nm. A slope efficiency of 49% with respect to the absorbed pump power was obtained for laser operation at 1032.5 nm. We studied the effects on the laser oscillation due to the reinjection of the residual pump. The thermal behavior of the sample was investigated by means of numerical simulations, accounting for the different thermal load resulting from spontaneous and laser emission. Finally, we report the measured level of the Amplified Spontaneous Emission, which is found to be less than 0.1 mW.